Answer:
-1 12⁄13
Step-by-step explanation:
-13x = 25 [Divide by -13]
x = -1 12⁄13
13 is your <em>divisor</em>, which will be your denominator, and the numerator is your <em>remainder</em><em>.</em><em> </em>Since 13 goes into 25 ONCE, 1 gets multiplied by 13 to get 13, then deduct that from 25 to get your remainder of 12. This is where you start putting the pieces together as a mixed number. Then attach the negative because whenever you divide a positive by a negative, you get a negative:
-25⁄13 = -1 12⁄13
I am joyous to assist you anytime.
*The answer is A. 24.*
All you have to do is back solve. In other words, just plug your answer choices into the equation.
I believe it would be (-2,-2) i may be wrong though i dont have my graphing papers
Answer:
x=2
x=-5
Step-by-step explanation:
You need to get everything on one side to have a quadratic equation:
x^2+6x-4 -(3x+6) = x^2+3x-10
All factors of 10 are 1*10 and 2*5.
5-2 = 3 and 5*-2 = -10
Factoring x^2+3x-10 gives us (x-2)(x+5)
x=2
x=-5
Answer:
no error original system so good by